Sufficient statistic or not? The elasticity of taxable income in the presence of deduction possibilities - Philipp Doerrenberg; Andreas Peichl; Sebastian Siegloch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The elasticity of taxable income (ETI) is often interpreted as a sufficient statistic to assess the welfare costs of taxation. Building on the conceptual framework of Chetty (2009), we show that this assertion does no longer hold for tax systems with deduction possibilities if (i) deductions generate externalities and (ii) deductions are responsive to tax rate changes. While the first condition should arguably hold for almost any imaginable tax deduction, we provide a thorough empirical examination of the second condition. Relying on rich German panel data from administrative tax records, we exploit several tax reforms that were implemented in Germany between 2001 and 2008. Our baseline estimates indicate an overall ETI of 0.49 and an elasticity of deductions with respect to the net-of-tax rate of -2.80. Given that the majority of deductions in the German income tax system generate externalities, our nonzero deduction elasticity suggests that the ETI is not sufficient to calculate the welfare cost of taxation.
Keywords: H24; H31; 330; elasticity of taxable income; deductions; tax expenditures; sufficient statistic; administrative data; Germany